2022
DOI: 10.1007/s41542-022-00128-6
|View full text |Cite
|
Sign up to set email alerts
|

“Are We Working (Too) Comfortably?”: Understanding the Nature of and Factors Associated with Sedentary Behaviour When Working in the Home Environment

Abstract: Home working has increased due to COVID-19, but little is known about how this change has impacted the health risk behaviour of elevated sedentary time. The aim of this cross-sectional exploratory study was to assess occupational sitting behaviour when working at home, and use the Capability Opportunity Motivation-Behaviour (COM-B) model to identify influences on this behaviour. University staff (n = 267; 69% female; 92% white) who were predominantly working from home completed a questionnaire to assess sittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
4
8
1
Order By: Relevance
“…First, a limiting factor for the generalizability of the study results is the Covid-19 pandemic situation during the data collection which may explain why the majority of participants indicated working from home at least partially. A recent study showed that working at home office is associated with high sedentary time and linked to different environmental and motivational determinants (Niven et al 2023 ). Therefore, study results may not be (fully) applicable to on-site work.…”
Section: Discussionmentioning
confidence: 99%
“…First, a limiting factor for the generalizability of the study results is the Covid-19 pandemic situation during the data collection which may explain why the majority of participants indicated working from home at least partially. A recent study showed that working at home office is associated with high sedentary time and linked to different environmental and motivational determinants (Niven et al 2023 ). Therefore, study results may not be (fully) applicable to on-site work.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the research on this topic has been carried out in workers who travel to their place of work, however, there has been an increase in homeworking following the Covid-19 pandemic with 24% of workers now reporting to follow a hybrid model of working (Office for National Statistics, 2022). In a study of homeworking (tele-working) university employees, staff spent almost 90% of their working time sitting (Niven et al, 2022) therefore strategies which can be employed to reduce prolonged sitting in the home-working environment are clearly required to reduce sedentary behaviour and associated ill health and disease risk. There has been research exploring the use of treadmill desks when working from home, which reports similar motivators to those found in our study, including an overwhelming desire to sit less and to 'feel healthier' (Scisco et al, 2023).…”
Section: Considerations In a Post-covid Eramentioning
confidence: 99%
“…Workers who used to commute to work, worked in an in-presence setting, and interacted with colleagues face-to-face, could now spend longer hours sitting in front of a computer screen [17]. Exacerbation of sedentary behavior may increase the risk for pain and discomfort as well as for adverse health outcomes [49][50][51][52], thus claiming specific attention in order to reduce sitting time in home workers. An increased prevalence of metabolic syndrome was reported for sedentary occupation types [53].…”
Section: Plos Onementioning
confidence: 99%